New challenges in the use of nutrition and health claims on milk and dairy products - Lea Pollak; Darija Vranešić Bender (Mljekarstvo)
By the Croatian accession to the European Union, a legal framework related to the use of nutrition and health claims on foods was adopted, as well as rules on informing consumers about food. Since milk and dairy products are traditionally positioned as healthy and nutritionally valuable products, adjusting to the new legislation is challenging for the dairy industry. After the evaluation process of health claims for nutrients naturally present in milk and dairy products, as well as those added in the production process, the European Food Safety Authority (EFSA) confirmed the beneficial effect of many active substances and established their recommended doses and effects. By the adoption of Commission Regulation (EU) No 432/2012 of 16 May 2012 a list of permitted health claims made on foods other than those referring to the reduction of disease risk and to children’s development and health was established. Also claims related to the impact of specific nutrients on the development and health of children were authorised by certain EU regulations. Nutrients in milk and dairy products related to nutrition and health claims are calcium, vitamin D, protein, yogurt culture, but also some active substances that are added to products such as different types of fibre, phytosterols and omega-3 fatty acids. By development of dairy products with special characteristics, such as those for specific population groups, it is possible to add nutrition claims which, for example, indicate a low energy value. This paper presents possibilities of application of nutrition and health claims on different types of products.